Mucinous Cystic Neoplasm of Liver: A Case Report from a Center in Kachchh District (GAIMS Journal of Medical Sciences, 2024)
Mucinous cystic neoplasms of the liver (MCN-L) are rare cystic tumors that occur within the liver parenchyma, or less frequently, in the extrahepatic bile ducts. Epidemiologic data are limited due to indolent nature of the tumor and recent changes to the diagnostic criteria proposed by World Health Organization (WHO). The etiology remains unclear, however female predominance, age of onset, and hormonally responsive ovarian-type stroma, suggest ectopic organogenesis during embryologic development. MCNs aretypically identified on imaging. Differentiation from common cystic lesions of liver is important for proper management. Complete excision is recommended for all lesions as malignant transformation has been reported.